High stability of photovoltaic cells with phenethylammonium iodide-passivated perovskite layers and printable copper phthalocyanine-modified carbon electrodes. (9th March 2021) - Wu, Yue; Wang, Shiyu; Ouyang, Tao; Li, Wenhui; Chen, Mingyue; Lu, Yu; Qi, Pengcheng; Tang, Yiwen
Abstract: Defects caused by the structural disorder of perovskites and voltage loss resulting from mismatched band structure are important issues to address to improve the performance of carbon-based perovskite solar cells. Different from the conventional approaches of additive-based passivation of perovskite precursors and introducing a hole-transport layer between the perovskite layer and carbon electrode, herein we report a defect-healing method using phenethyl ammonium iodide (PEAI) treatment and band-structure modification using high-work-function inorganic copper phthalocyanine (CuPc). Because of its relatively smoother surfaces and lower defect content, the optimized device after PEAI-based passivation of the perovskite achieves a power conversion efficiency (PCE) of 11.74%. The PCE is further raised to 13.41% through the auxiliary energy-level matching and high hole extraction abilities of the CuPc-modified carbon electrode. The best-performing device exhibits excellent moisture tolerance and thermal stability with minor current density–voltage hysteresis.